Challenging Past and Present : the Metamorphosis of Nineteenth-Century Japanese Art - Conant, Ellen P. (University of Hawaii Press, 2006)
The complex and coherent development of Japanese art during the course of the nineteenth century was inadvertently disrupted by a political event: the Meiji Restoration of 1868. Scholars of both the preceding Edo (1615-1868) and the succeeding Meiji (1868-1912) eras have shunned the decades bordering this arbitrary divide, thus creating an art-historical void that the former view as a period of waning technical and creative inventiveness and the latter as one threatened by Meiji reforms and indiscriminate westernization and modernization. Challenging Past and Present, to the contrary, demonstrates that the period 1840-1890, as seen progressively rather than retrospectively, experienced a dramatic transformation in the visual arts, which in turn made possible the creative achievements of the twentieth century. The first group of chapters takes as its theme the diverse cultural currents of the transitional period, particularly as they applied to art. The second section deals with the inconsistent yet determinedly pragmatic courses pursed by artists, entrepreneurs, and patrons to achieve a secure footing in the uncertain terrain of early Meiji. Further chapters look at how painters and sculptors sought to absorb and integrate foreign influences and reinterpret their own stylistic mediums.